Microbial agents in macroscopically healthy mammary gland tissues of small ruminants - Spuria, Liliana; Biasibetti, Elena; Bisanzio, Donal; Biasato, Ilaria; De Meneghi, Daniele; Nebbia, Patrizia; Robino, Patrizia; Bianco, Paolo; Lamberti, Michele; Caruso, Claudio; Di Blasio, Alessia; Peletto, Simone; et al. (PeerJ, 2017)
Background Health of mammary glands is fundamental for milk and dairy products hygiene and quality, with huge impacts on consumers welfare. Methods This study aims to investigate the microbial agents (bacteria, fungi and lentiviruses) isolated from 89 macroscopically healthy udders of regularly slaughtered small ruminants (41 sheep, 48 goats), also correlating their presence with the histological findings. Multinomial logistic regression was applied to evaluate the association between lesions and positivity for different microbial isolates, animal age and bacteria. Results Twenty-five samples were microbiologically negative; 138 different bacteria were isolated in 64 positive udders. Coagulase-negative staphylococci were the most prevalent bacteria isolated (46.42%), followed by environmental opportunists (34.76%), others (10.14%) and pathogens (8.68%). Most mammary glands showed coinfections (75%). Lentiviruses were detected in 39.3% of samples. Histologically, chronic non-suppurative mastitis was observed in 45/89 glands, followed by chronic mixed mastitis (12/89) and acute suppurative mastitis (4/89). Only 28 udders were normal. Histological lesions were significantly associated with the animal species and lentiviruses and coagulase-negative staphylococci infections. Goats had significantly higher risk to show chronic mixed mastitis compared to sheep. Goats showed a significantly lower risk (OR = 0.26; 95% CI [0.06–0.71]) of being infected by environmental opportunists compared to sheep, but higher risk (OR = 10.87; 95% CI [3.69–37.77]) of being infected with lentiviruses. Discussion The results of the present study suggest that macroscopically healthy glands of small ruminants could act as a reservoir of microbial agents for susceptible animals, representing a potential risk factor for the widespread of acute or chronic infection in the flock.
Keywords: Small ruminants; Microbiology; Histology; Healthy mammary gland